A study on prevalence of myopia and its associated factors in school children of Salem, Tamil Nadu - K., Chellavel Ganapathi; R, Arun Vijay Paul; K., Kokila; S., Bharath Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Myopia is the major refractive error having a worldwide prevalence of 1.5 billion. Children with Myopia feel difficulties in viewing blackboard in school; they avoid outdoor activities and get isolated from the peer groups. Untreated myopia may lead to Macular degeneration, Glaucoma, Cataract, Retinal detachment. Thus this study was carried out. The aim of the study to find out the prevalence of myopia among school children and its associated factors. Methods: The study was a cross sectional study carried out among students of government higher secondary school, Sarkar Kollapatti, Salem. Total sample size of 854 Students from class 6-12 was selected by simple random sampling. Students were examined by Snellen’s chart, non-cycloplegic auto refractometry and by pin hole test. Finally all data were entered in EPIDATA and analysed in IBM SPSS software version 20. Results: After complete analysis, prevalence of myopia was 11.7% of which 46% were boys and 54% were girls. Among students of age 8 to 19 years, the most common age group involved was 14-17 years of age followed by students of 10-13 years of age. Time spent on visual gadgets was the major factor associated with myopia. Familial predisposition, average amount of time a person spends on near work showed significant association with myopia. Conclusions: This study throws light on prevalence of myopia in semi-urban school children & various factors associated with myopia. Students with myopia were referred to Department of Ophthalmology, GMKMCH and thus they were prevented from further complications due to myopia and improve the academic performance.